2022
DOI: 10.1038/s41598-022-05573-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro assay of hydroxyxanthones as antioxidant and anticancer agents

Abstract: In the present work, three hydroxyxanthones were synthesized in 11.15–33.42% yield from 2,6-dihydroxybenzoic acid as the starting material. The chemical structures of prepared hydroxyxanthones have been elucidated by using spectroscopic techniques. Afterward, the hydroxyxanthones were evaluated as antioxidant agents through radical scavenging assay; and anticancer agents through in vitro assays against WiDr, MCF-7, and HeLa cancer cell lines. Hydroxyxanthone 3b was categorized as a strong antioxidant agent (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Fatmasari et al. (2021) reported that the addition of one hydroxyl group on xanthone derivatives decreased their anticancer activity [32] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatmasari et al. (2021) reported that the addition of one hydroxyl group on xanthone derivatives decreased their anticancer activity [32] …”
Section: Resultsmentioning
confidence: 99%
“…Fatmasari et al (2021) reported that the addition of one hydroxyl group on xanthone derivatives decreased their anticancer activity. [32] The anticancer activity of compounds on their inhibition of cell growth was classified into three types: active as anticancer (IC 50 < 20 μg/mL), moderate as anticancer (IC 50 20-100 μg/mL), and inactive as anticancer (IC 50 > 100 μg/mL). [36] Based on the reference, thioxanthone TX3 had moderate activity against T47D (IC 50 86.01 μg/mL), but was inactive against HeLa, A549, and WiDr (IC 50 > 100 μg/mL).…”
Section: Anticancer Activity Assay Of Thioxanthonesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was thoroughly reported that introducing additional substituents to the xanthone skeleton enhances its anticancer activity significantly. For instance, Fatmasari et al [7] reported the synthesis of oxygenated xanthones as the anticancer agent against HeLa, WiDr, and MCF-7; however, these compounds were found to be toxic to normal cells. On the other hand, Yuanita et al [8] have synthesized new xanthone derivatives through the attachment of halogen groups into oxygenated xanthones.…”
Section: ■ Introductionmentioning
confidence: 99%